2021
DOI: 10.1371/journal.ppat.1009618
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Plasticity Enables CNS-Trafficking of EBV-infected B Lymphocytes

Abstract: Subpopulations of B-lymphocytes traffic to different sites and organs to provide diverse and tissue-specific functions. Here, we provide evidence that epigenetic differences confer a neuroinvasive phenotype. An EBV+ B cell lymphoma cell line (M14) with low frequency trafficking to the CNS was neuroadapted to generate a highly neuroinvasive B-cell population (MUN14). MUN14 B cells efficiently infiltrated the CNS within one week and produced neurological pathologies. We compared the gene expression profiles of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 102 publications
0
29
0
Order By: Relevance
“…Studies in MS patients and animal models have identified gene variants, miRNAs and viral co-factors that exert epigenetic control to increase inflammation, immune cell differentiation and myelin breakdown 189 . Epigenetic modification of genes that promote neuroinvasion of EBV-positive B cells, including the genes encoding osteopontin and CXCR4, has been described in some experimental models, suggesting that EBV may affect epigenetic mechanisms driving MS 190 .…”
Section: How Does Ebv Increase the Risk Of Ms?mentioning
confidence: 99%
“…Studies in MS patients and animal models have identified gene variants, miRNAs and viral co-factors that exert epigenetic control to increase inflammation, immune cell differentiation and myelin breakdown 189 . Epigenetic modification of genes that promote neuroinvasion of EBV-positive B cells, including the genes encoding osteopontin and CXCR4, has been described in some experimental models, suggesting that EBV may affect epigenetic mechanisms driving MS 190 .…”
Section: How Does Ebv Increase the Risk Of Ms?mentioning
confidence: 99%
“…Thus, EBV-associated autoimmune diseases, regardless of the cellular or humoral autoreactive response, could be at an increased risk of developing cancer over the years, as is the case in MS [ 174 ] or RA [ 23 , 190 , 191 ]. Thus, the presence of B cells with EBV latency in ectopic lymphoid structures in the tissue where the autoimmune response develops could lead to the development of B-cell lymphoma, as has been observed in the salivary glands in Sjögren’s syndrome [ 258 , 259 , 260 , 261 ], in the thyroid gland in autoimmune thyroiditis [ 220 , 262 , 263 , 264 ], and in the central nervous system in MS [ 265 , 266 ]. Even first-degree relatives of patients with MS have an increased susceptibility for developing Hodgkin’s lymphoma, suggesting that the same environmental factor (EBV infection) in a family environment with similar genetic factors (HLA class II) could predispose some to develop an autoimmune disease, and for others, cancer [ 175 , 176 , 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may mechanistically implicate this chemokine in the migration of virus infected cells to the CNS. Furthermore, EBV infected B cells with phosphoprotein 1/osteopontin gene upregulation have been found to have the potential of infiltrating the CNS ( 45 ). The gene upregulation in these cells is associated with epigenetic changes including histone modification.…”
Section: Discussionmentioning
confidence: 99%